Is Bandung Wifi Juara Program Success? - Robi Gustia (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2018)
The purpose of this study was to determine the public perception of Bandung Juara Wifi program 2013-2015. In this research, there are attributes Bandung Juara Wifi used to determine the public perception that consists of Internet access services, internet access tool, the cost of internet access, internet access time and service packs. The sampling technique used in this research is purposive sampling so as to produce the 400 respondents who answered the questionnaire. This research data analysis technique is univariate data analysis techniques. The results of this study stated that overall public perception of the Bandung Juara Wifi is good. But needs to be improved on one attribute, namely, the services pack by improving the speed and stability of the Internet that are owned by Bandung Juara Wifi.